276 Review of endometrial cancer management at an upcoming gynaecological oncology unit in India. (13th November 2020) - Digumarti, L; Vemanamandhi, P; Digumarti, R
Abstract : Aim: Analyse the presentation and management of endometrial cancer in a newly established gynaecological oncology unit in an upcoming cancer hospital. Methods: Retrospective analysis of all endometrial cancer patients managed in the unit between April 2015 and June 2020. Results: A total of 54 women with uterine corpus cancers were seen. The commonest complaint was post menopausal bleeding. Of these, 41 are endometrioid adenocarcinomas. The age distribution is as follows: <50 years: 6, >50 years: 35 (85%). Majority had 2 children. The commonest co-morbidities were hypertension (21) and diabetes (18). The BMI (Asian standards) was >25 (overweight & obese) in 31 women. The predominant preoperative histologic grade on endometrial biopsy was grade 1 (17/41). Preoperative MR Imaging showed myometrial invasion of <50% in 13/41 (31%), >50% in 6/41 (14%). All women had primary surgical staging except a lone patient with lung metastases. The surgical staging showed that 27 (65%) had stage 1A, 8 were in 1B (19.5%) and the rest 5 in stage 3 (12.19%). All women with stage 3 disease had LVSI. According to ESGO-ESMO-ESTRO risk stratification, 22 (53.6%) were in low risk, while 9 (21.9%) in high risk and remaining 9 (21.9%) were in intermediate risk. Adjuvant chemotherapy, radiation therapy or combination was given according to this risk classification. Two women, who refused adjuvant treatment, died of recurrence. All patients are on regular follow-up. Conclusions: Timely evaluation of post menopausal bleeding helps in the diagnosis and management of endometrial cancer.